Efek Antihiperglikemik Kombinasi Ekstrak Etanol Cocor Bebek (Kalanchoe pinnata) dan Lidah Buaya (Aloe vera) pada Mencit yang Diinduksi Aloksan: Antihyperglycemic Effects of Combined Ethanolic Extracts of Cocor Bebek (Kalanchoe pinnata) and Lidah Buaya (Aloe vera) in Alloxan-Induced Mice - Agusriani; Halimatusa'diyah; Karin Tika Fitria; Egy Sunanda Putra (Amerta Nutrition, 2026)
Background: Hyperglycemia is a hallmark of diabetes mellitus and contributes significantly to the development of systemic complications. Plant-based antihyperglycemic agents have gained increasing attention as alternative therapies due to their bioactive compounds and relatively low side effects. However, evidence on the combined effects of Kalanchoe pinnata (cocor bebek) and Aloe vera (lidah buaya) remains limited. Objectives: This study aimed to evaluate the glucose-lowering effects of combined ethanolic extracts of Kalanchoe pinnata and Aloe vera leaves in alloxan-induced hyperglycemic mice. Methods: Leaves were dried, powdered, and extracted with 96% ethanol via maceration, followed by filtration, evaporation, and freeze-drying. A total of 25 male mice were randomly divided into five groups (n=5 per group): negative control, positive control (glibenclamide), and three treatment groups receiving combined extracts at doses of 200, 400, and 800 mg/kg body weight. Hyperglycemia was induced using alloxan (150 mg/kg BW), and mice were considered hyperglycemic when blood glucose exceeded 176 mg/dL. Blood glucose levels were measured at 0, 30, 60, and 90 minutes post-treatment. Results: Minimal glucose reduction was observed in the negative control group (1.64-3.63%), while the positive control showed the greatest decrease (29.81-59.28%). The treatment groups demonstrated a dose-dependent effect, with reductions of 17.61%, 24.52%, and 32.80% at doses of 200, 400, and 800 mg/kg BW, respectively. Statistical analysis showed significant differences among groups (p<0.001) and between doses (p=0.016). Conclusions: These findings suggest that combined extracts of Kalanchoe pinnata and Aloe vera exhibit significant antihyperglycemic activity in alloxan-induced mice.